2019
DOI: 10.3390/agronomy9090522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Deficit Stress on Seedling Biomass and Physio-Chemical Characteristics in Different Species of Wheat Possessing the D Genome

Abstract: Wild relatives of wheat serve as an extraordinary source of variability for breeding programs due to their capabilities to respond to various environmental stresses. Here, we investigated some species possessing a D genome (T. aestivum, Ae. tauschii, Ae. crassa and Ae. cylindrica) in terms of relative water content (RWC), stomatal conductance (Gs), relative chlorophyll content, initial fluorescence (Fo), maximum quantum yield of PSII (Fv/Fm), maximum primary yield of PSII photochemistry (Fv/Fo), as well as sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 61 publications
9
28
3
Order By: Relevance
“…This result indicates that some of the tested genotypes (especially G9) may have a strong capacity to protect themselves through maintenance of high levels of PSII activity. Although several studies reported that drought stress reduces Fv/Fm [1,17,29], our results revealed that the process of energy displacement from the antenna chlorophyll complex to the PSII may not be affected by drought stress in some of the tested genotypes. The stomatal conductance (Gs) as a physiological trait has two important roles: (1) maintenance of water in leaf tissue by control of transpiration, and (2) determining the rate of gas exchange by movement of gases between the inner and outer environments of the leaf tissue.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…This result indicates that some of the tested genotypes (especially G9) may have a strong capacity to protect themselves through maintenance of high levels of PSII activity. Although several studies reported that drought stress reduces Fv/Fm [1,17,29], our results revealed that the process of energy displacement from the antenna chlorophyll complex to the PSII may not be affected by drought stress in some of the tested genotypes. The stomatal conductance (Gs) as a physiological trait has two important roles: (1) maintenance of water in leaf tissue by control of transpiration, and (2) determining the rate of gas exchange by movement of gases between the inner and outer environments of the leaf tissue.…”
Section: Discussioncontrasting
confidence: 76%
“…Among the yield-based indices, STI is a suitable index for characterization of the most tolerant to drought stress. Indeed, its applicability has been confirmed in numerous studies [1,17,22,29,35,38,41,42]. Based on the three-dimensional plots, several different genotypes were distributed in Group A each year ( Figure S2).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Depending on the growth stage, intensity and duration of the stress, and nature of plant stress response mechanisms; drought stress causes a decrease in RWC, chlorophyll degradation, stomatal closure, increased osmolytes, and growth inhibition in wheat [32][33][34][35] which ultimately leading to yield loss and productivity. Previous reports demonstrated that water deficit (drought stress) in wheat [36,37] has unfavorable effects on the efficiency of photosystem II (PSII), as indicated by changes in chlorophyll florescence (CF) [38] parameters such as initial fluorescence (Fo), maximum quantum yield of PSII (Fv/Fm), maximum primary yield of PSII photochemistry (Fv/Fo), as well as plant growth and dry matter. Therefore, understanding crop stress physiology and its related tools such as chlorophyll fluorescence (CF) has become known as a useful indicator for investigating stress in plants in vivo [39].…”
Section: Introductionmentioning
confidence: 99%